2018
DOI: 10.1177/1403494818779853
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in child and adolescent health in the Scandinavian welfare states: The role of parental socioeconomic status – a systematic review

Abstract: Overall poorer health outcomes in non-Western immigrant compared with majority children in Scandinavia cannot be fully explained by SES. Evidence points to additional mechanisms at individual, household, societal or policy levels, including reasons for migration, culture and societal discrimination. Finally, methodological issues may influence study outcomes, e.g. heterogeneity of populations studied and socioeconomic variables included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 57 publications
6
41
2
1
Order By: Relevance
“…7,17 Although immigrants represent a lower socioeconomic status group than native inhabitants in most societies, studies from Scandinavian countries have shown that children's health status varies according to social conditions among participants with and without immigrant status. 4 Moreover, the present findings showed that the TPB components, attitudes, subjective norms, and perceived behavioral control, were independent significant covariates of parental intention to brush children's teeth, explaining about 41% of its variance. This supports the TPB in predicting immigrant parents' intention to take care of their children's oral health from an early age and is consistent with previous research regarding older pre-school children's tooth brushing behavior.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…7,17 Although immigrants represent a lower socioeconomic status group than native inhabitants in most societies, studies from Scandinavian countries have shown that children's health status varies according to social conditions among participants with and without immigrant status. 4 Moreover, the present findings showed that the TPB components, attitudes, subjective norms, and perceived behavioral control, were independent significant covariates of parental intention to brush children's teeth, explaining about 41% of its variance. This supports the TPB in predicting immigrant parents' intention to take care of their children's oral health from an early age and is consistent with previous research regarding older pre-school children's tooth brushing behavior.…”
Section: Discussionsupporting
confidence: 48%
“…2,3 Several studies have shown that people with immigrant background have more socioeconomic difficulties, poorer well-being status, and suffer more from lifestyle-and diet-related disorders compared to the native population. 4 Moreover, evidence suggests that children of immigrant parents are at greater risk of diverse health problems than are their host country counterparts. 4 According to the American Academy of Pediatric Dentistry, early childhood caries (ECC) is any form of caries (cavitated and non-cavitated) occurring in the primary dentition of children aged 6 years or less.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Una búsqueda en PubMed (https://www.ncbi.nlm.nih.gov/ pubmed/), usando lenguaje libre mediante las palabras «immigrant OR migrant» AND «health», sin la aplicación de términos MeSH, da cuenta de 212 revisiones sistemáticas de diversos temas en salud en los últimos cinco años. De éstas, siete (3,3%) se ocupan de investigar temas relacionados con migración y salud bucal (10)(11)(12)(13)(14)(15)(16) . Esto da pie a la necesidad de analizar la situación de salud bucal desde un enfoque de los determinantes sociales que permita identificar las necesidades específicas en diferentes grupos sociales como la población migrante.…”
Section: Introductionunclassified